Preclassical conflict of laws - Hatzimihail, Nikitas (Cambridge : Cambridge University Press, 2021)
To better appreciate present-day private international law and its future prospects and challenges, we should consider the history and historiography of the field. This book offers an original approach to the study of conflict of laws and legal history that exposes doctrinal lawyers to historical context, and legal historians to the intricacies of legal doctrine. The analysis is based on an in-depth examination of Medieval and Early Modern conflict of laws, focusing on the classic texts of Bartolus and Huber. Combining theoretical insights, textual analysis and historical perspectives, the author presents the preclassical conflict of laws as a rich world of doctrines and policies, theory and practice, context and continuity. This book challenges preconceptions and serves as an advanced introduction which illustrates the relevance of history in commanding private international law, while aspiring to make private international law relevant for history.
Historical literature and historical consciousness in contemporary private international law -- Preclassical conflict of laws in modern historical consciousness -- Conflict of laws as a conceptual battlefield -- Conflict of laws as a doctrinal exercise -- Conflict of laws in a world-system -- "Nunc veniamus ad glossam" : bartolus comments oncunctos populos -- Bartolus in a world-system -- Bartolan conflicts as a doctrinal exercise -- Bartolus and the modern consciousness -- "It often happens that transactions..." : Huber on the conflict of laws -- The world-system of Huber's conflict of laws -- Huber's conflict of laws as a doctrinal work -- Huber and the modern consciousness -- Preclassical conflict of laws configured.
Title from publisher's bibliographic system (viewed on 12 Jul 2021).
Keywords: Conflict of laws -- History